2020
DOI: 10.3390/environments7100075
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of GIS-Land Use Suitability in the Rural–Urban Continuum between Ar Riyadh and Al Kharj Cities, KSA Based on the Integrating GIS Multi Criteria Decision Analysis and Analytic Hierarchy Process

Abstract: The management of land use in big cities and capitals and the surrounding adjacent urban aggregates is still of major importance in the field of urban development, especially in cities with populations of millions and various types of land uses and economic activities. The rural–urban continuum between the cities of Ar Riyadh and Al Kharj suffers from an unclear general land use trend, due to urban expansion at the expense of the agriculture lands, the imbalance of the population compound, the deterioration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…For instance, topographic factors, such as slope and elevation, were found as some of the main driving factors for SUD in cities [19,37]. The accessibility to social activities and economic opportunities, represented by the distance from residential, commercial, and industrial areas, was also found as an essential element in defining the suitable location for SUD [13,38,39]. This requirement is highly provided by compact urban fabrics.…”
Section: Developed Methodologymentioning
confidence: 99%
“…For instance, topographic factors, such as slope and elevation, were found as some of the main driving factors for SUD in cities [19,37]. The accessibility to social activities and economic opportunities, represented by the distance from residential, commercial, and industrial areas, was also found as an essential element in defining the suitable location for SUD [13,38,39]. This requirement is highly provided by compact urban fabrics.…”
Section: Developed Methodologymentioning
confidence: 99%
“…This entails good planning, consideration of environmental sustainability, and attention to the social changes that could result from the development. Land use decisions for sustainable urban development require consideration of various physical, environmental, demographic, natural, economic, planning, social, and managerial factors (Karim et al, 2020).…”
Section: Identification Of Regional Potential Capital City Developmen...mentioning
confidence: 99%
“…This method plays an important role in urban planning by comprehensively analysing spatial data, identifying potential development areas, and proposing optimal land use strategies (Zakarya et al, 2021). Land suitability evaluation includes assessing suitable areas for development by determining the suitability index of a particular area (Karim et al, 2020). It is considered the best and most effective method for finding areas that suit different parameters or criteria influencing the decision to settle in a place (Saha & Roy, 2021).…”
Section: Identification Of Regional Potential Capital City Developmen...mentioning
confidence: 99%
“…Rural-urban migration resulted in rapid urbanization, and people began settling in the cities and their surroundings. This increased the number of surfaces made of asphalt and other hard materials [2], which had a severe impact on natural ecosystems and might have even led to a radical loss in these ecosystems [1,3]. Although urban spaces cover only 2% of the surface of the earth, they emit considerable amounts of greenhouse gases and more than 70% of global CO 2 emissions; this is due to the heavy use of fossil fuels for transportation, heating, etc.…”
Section: Introductionmentioning
confidence: 99%